2019
DOI: 10.1002/jbt.22400
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of eriocitrin against the dextran sulfate sodium–induced experimental colitis in murine model

Abstract: Inflammatory bowel disease (IBD) is a continual ailment condition which engrosses the entire alimentary canal. The IBD can be primarily distinguished into two forms, ulcerative colitis, and Crohn's disease. The major symptoms of IBD include pustules or abscesses, severe abdominal pain, diarrhea, fistula, and stenosis, which may directly affect the patient's quality of life. A variety of mediators can stimulate the circumstances of IBD, some examples include infections by microbes such as bacteria, perturbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In addition, feeding mice MetOH extract partly, but significantly, reduced DSS-induced Cxcl2 expression in colonic tissues. Previous studies showed that oral administration of hesperidin (10-40 mg/kg bodyweight) and eriocitrin (20 mg/kg bodyweight) reduces disease symptoms in DSS-induced colitic mice [56,57]. The doses of hesperidin and eriocitrin achieved through feeding mice whole LP powder and MetOH extract were approximately equivalent to 17 and 7 mg/kg bodyweight, respectively, under the feeding conditions of this study.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, feeding mice MetOH extract partly, but significantly, reduced DSS-induced Cxcl2 expression in colonic tissues. Previous studies showed that oral administration of hesperidin (10-40 mg/kg bodyweight) and eriocitrin (20 mg/kg bodyweight) reduces disease symptoms in DSS-induced colitic mice [56,57]. The doses of hesperidin and eriocitrin achieved through feeding mice whole LP powder and MetOH extract were approximately equivalent to 17 and 7 mg/kg bodyweight, respectively, under the feeding conditions of this study.…”
Section: Discussionsupporting
confidence: 52%
“…Eriocitrin is a flavonoid compound mainly derived from lemon or citrate juice. It is known to exert protective effects on human health (3), and to possess anti-diabetic, anticarcinogenic, antioxidative, and anti-steatotic pharmacological benefits (4). Some scholars have reported that eriocitrin also attenuates oxidative damage in rat liver tissues (5).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2016 ( 1 ), a limited number of new molecules have been tested in animal model studies of IBD ( Table 2 ). These include betulinic acid ( 57 ), goat whey ( 58 ), polyphenols ( 59 ), eriocitrin ( 60 ), proglitazone ( 61 ), dietary products from grape seeds ( 62 , 67 ) and lupin extracts ( 63 ) and traditional Chinese herbal preparations ( 64 ). In clinical studies, a cannabinoid receptor 2 agonist was found to improve mucosal healing ( 65 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%